PENERAPAN DOKTRIN PIERCING THE CORPORATE VEIL DALAM PRAKTEK PERSEROAN TERBATAS DALAM PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA (MARI), (STUDI PUTUSAN PERKARA NOMOR 1916K/PDT/1991 DAN NOMOR 1311K/PDT/2012) - JEFFRY LEANDER (PREMISE LAW JURNAL, 2017)
The main character of a limited liability company is that it is a legal subject which status is as a legal entity and liability is limited (limited liability) to the shareholders, members of board of directors and commissionairs i.e. as much as the shares they have in the company in accordance with the provisions in Article 3 paragraph (1) of the Law No.40/2007. However, in certain things, this liability is possibly eliminated by the principle of piercing the corporate veil. The research problems are how this Piercing the Corporate Veil is implemented in the laws and regulation concerning the limited liability companies in Indonesia, how this principle is regulated in relation with the board of directors of limited liability companies in Indonesia, and how the comparison of the Ruling of the Supreme Court of the Republic of Indonesia related to the Piercing the Corporate Veil Doctrine before the issuance of the Law No. 1/1995 until it was amended into the Law No.40/2007 on Limited Liability Companies between the Ruling of the Supreme Court for the Case No.1916 K/Pdt/1991 and 1311 K/Pdt/2012.Keyword: Piercing the Corporate Veil; limited liability; directors